Adaptation of the MAS to deaf speech (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The aim of the present study was to adapt the Analogic Mood Scale for hearing impaired individuals speaking Brazilian Sign Language (LIBRAS) and talking by the finger alphabet, yielding a bilingual scale. The sample of Study was composed of 15 hearing impaired individuals talking by the finger alphabet and LIBRAS and 40 normal hearing individuals aged 11 to 18 years of both genders. After previous training, the participants filled a version of the scale according to the characteristics of their group, in Portuguese or in LIBRAS. The scales were applied in group. The results showed that both versions of the analogue mood scale were equivalent, because no-statistical significant differences in the total index and in the components of the scale (anxiety, physical sedation and mental sedation) were related. The only factor presenting statistically significant difference was the presence of other feelings. Such results suggest the possibility of use of this scale for studies of anxiety among hearing impaired patients.